A Non-Invasive Scoring System to Differential Diagnosis of Clear Cell Renal Cell Carcinoma (ccRCC) From Renal Angiomyolipoma Without Visible Fat (RAML-wvf) Based on CT Features - Wang, Xiao-Jie; Qu, Bai-Qiang; Zhou, Jia-Ping; Zhou, Qiao-Mei; Lu, Yuan-Fei; Pan, Yao; Xu, Jian-Xia; Miu, You-You; Wang, Hong-Qing; Yu, Ri-Sheng (Frontiers in Oncology, 2021)
Background: Renal angiomyolipoma without visible fat (RAML-wvf) and clear cell renal cell carcinoma (ccRCC) have many overlapping features on imaging, posing a challenge to radiologists. This study aimed to create a scoring system to distinguish ccRCC from RAML-wvf in computed tomography imaging. Methods: A total of 202 patients (2011–2019) that were pathologically confirmed with ccRCC (n=123) or RAML (n=79) were retrospectively analyzed by randomly dividing them into a training cohort (n=142) and a validation cohort (n=60). A model was established by logistic regression, and it was weighted to be a scoring system. The ROC, AUC, cut-off point, and calibration analyses were performed. The scoring system was divided into three groups for convenience in clinical evaluations, and the diagnostic probability of ccRCC was calculated. Results: Four computed tomography features were incorporated into the scoring system. The prediction accuracy had an ROC of 0.978 (95% CI, 0.956–0.999; P=0.011), similar to the primary model (ROC, 0.977; 95% CI, 0.954–1.000; P=0.012). A sensitivity of 91.4% and a specificity of 93.9% were achieved using 4.5 points as the cutoff value. Validation showed a good result (ROC, 0.922; 95% CI, 0.854–0.991, P=0.035). Patients with ccRCC among the three groups (≥0 to <2 points; ≥2 to ≤4 points; >4 to ≤11 points) significantly increased with increasing scores. Conclusion: This scoring system is convenient for distinguishing between ccRCC and RAML-wvf by observing four critical computed tomography features.